Wii-bändi : designing an expressive digital musical interface for therapeutic use with disabled people in a group setting - Reed, Alexander (2011)
This thesis presents the developmental prototype of a gesturally controlled digital musical interface. It is called Wii-bändi, as it uses Nintendo Wii controllers to translate the gestures into music, and is constructed specifically for clients with a variety of physical and mental disabilities so that they can use it in a therapeutic group context. It is argued that gestural and emotional expressivity might be based on a theory of vitality affects, and that optimal learnability could be achieved through making use of learning schemas. It then sets out how the interface was created using a methodological approach based on action research, describing the specific contexts that led to the changes that were made to the set-up, over a period of approximately one year (between November, 2008 and December, 2009). The research is split into three cycles. The first explores the specific wishes of the group in question, establishing the core members and core values for the group who are to use the interface; the second progressively develops the interface along those lines as far as is possible, given the limits of the technological tools available; and the third consolidates what has been achieved by finding the optimal way to use the interface constructed. This was found to be a form of musical role play which is covered in greater detail in the last chapter of results. Finally, there is discussion of how best to avoid some of the technical issues that befell Wii-bändi, and the conclusion describes how the interface presents a viable model for using modern music technology to work with disabled people in the future.